A graphene-directed assembly route to hierarchically porous Co–Nx/C catalysts for high-performance oxygen reduction1. Issue 32 (28th August 2015) - Wei, Jing; Hu, Yaoxin; Wu, Zhangxiong; Liang, Yan; Leong, Sookwan; Kong, Biao; Zhang, Xinyi; Zhao, Dongyuan; Simon, George P.; Wang, Huanting
<x xml:space="preserve">Abstract</x> Graphene-directed assembly of ZIF nanocrystal arrays was developed to synthesize hierarchically nanoporous Co–Nx/C materials. The resulting materials exhibit high ORR catalytic activity and superior stability under both alkaline and acidic conditions.